PENGEMBANGAN MODEL KEPEMIMPINAN TRANSFORMASIONAL (Fokus Ekonomi, 2008)
Base on the leadership theory and research shows that transformational leadership is morepromising to sustain the success of the organization, especially the influence of organizationsthat are facing global business today. Development of a transformational leadership modelthat was developed by the authors to adopt and modify the effective transformationalleadership model proposed by Locke and friends. Development of a transformationalleadership model is composed of five parts, namely: 1) the motives and character, 2)knowledge, skill, and ability, 3) organizational culture, 4) vision, and 5)implementation of the vision.Key words: transformational, leadership, organization.